O processo de constituição do gênero discursivo “desenho infantil escolar”: um olhar sobre o ato narrativo de desenhar - Silva, Wellington Barbosa (2015)
The contemporary reflections on the process of constitution of different genres have constantly discussed and put into evidence the contributions of Mikhail Bakhtin and his circle called, whose ideas have been currently great influence on scholars from different fields of humanities and social sciences and epistemological ruptures caused on human language. In this new situation, incorporated into a language of sociointeractionist design in which the dialogical and discursive interaction are presented as the language of the reality of their own spaces, since it is here that gives the production of statements, while activity of subjects in processes of social communication. This movement is therefore a work that develops in different social contexts and that is at the same time constitutive of language and of the participating subjects of discursive interactions. In this new way of designing and producing different forms of language, we can say that the children who will find the beginning of the schooling process make use of a particular way of writing representation, producing interpretations, own speeches and subscribing to a discourse, marked by a kind of abstraction that determines its own form of rationality and individualization in their discursive productions. With this vision, we understand that within the teaching and language learning process, especially the discursive production, a given presents itself as a proper element of the written language acquisition process, which is the production by students, the act narrative drawing as a form of representations of ideas, feelings, and especially the reality around him. Thus, this paper analyzes the role of narrative act of drawing in the generation process of discursive genre "school children's drawing" and through this analysis, observe marks of individual work of children with language that could be taken as evidence a style in constitution. Then we can look at individual histories of involvement with the language and get these stories features that single out, making it possible to think of a design style as "choice" as a mark of the work of the subject with the language. For this, we adopted the methodology of qualitative research, more specifically, the collaborative research Desgagné (2001), with a multidisciplinary approach supported in the possibilities of working within the interpretive research. The theoretical framework adopted articulates concepts of discursive enunciative theory Bakhtin, Vygotsky sociointeractionist of learning theory, Cultural psychology Bruner and phenomenology of Merleau-Ponty. Finally, we come to the understanding that the narrative act of drawing children is the way in which children take ownership of speeches and symbolic elements to exercise their autonomy through the existing textuality and produce the discursive gender school children's drawing, as possibility of analysis of social reality and manifestation of their discursive intentions.